PENGARUH METODE BAGIAN TERHADAP KEMAMPUAN JURUS 3 SENI TUNGGAL GOLOK DI SEKOLAH DASAR KARTIKA - Lestari, Dwi Suci (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problem of research is whether there is influence of the part method on the skill of single arts skill in students at Kartika Elementary School. The purpose of this research is to know the influence of the part method on the ability of 3 arts of single arts of machetes at the students in Kartika Elementary School. The method used in this research is experimental method with Pre-experiment design. The study population took all the extracurricular students in Kartika Elementary School, which amounted to 15 people. Sample technique with saturated sampling technique that is all of extracurricular students in Kartika Primary School Pontianak, amounting to 15 people. Analysis of data used using t-test analysis. The result of the research is that the value of ttest = 4.245 is bigger than ttable value = 2.145, with the effect of size increase of 0.86. Based on these results it can be concluded that there is influence of the influence of part method on the ability of 3 statues single arts machetes in extracurricular students in elementary school Kartika Pontianak.Â Keywords: Part Method, Kick 3 The Single Art of MacheteÂ